Genome-Wide Analysis of Targets for Post-Transcriptional Regulation by Rsm Proteins in Pseudomonas putida - Huertas-Rosales, Óscar; Romero, Manuel; Chan, Kok-Gan; Hong, Kar-Wai; Cámara, Miguel; Heeb, Stephan; Barrientos-Moreno, Laura; Molina-Henares, María Antonia; Travieso, María L.; Ramos-González, María Isabel; Espinosa-Urgel, Manuel (Frontiers in Molecular Biosciences, 2021)
Post-transcriptional regulation is an important step in the control of bacterial gene expression in response to environmental and cellular signals. Pseudomonas putida KT2440 harbors three known members of the CsrA/RsmA family of post-transcriptional regulators: RsmA, RsmE and RsmI. We have carried out a global analysis to identify RNA sequences bound in vivo by each of these proteins. Affinity purification and sequencing of RNA molecules associated with Rsm proteins were used to discover direct binding targets, corresponding to 437 unique RNA molecules, 75 of them being common to the three proteins. Relevant targets include genes encoding proteins involved in signal transduction and regulation, metabolism, transport and secretion, stress responses, and the turnover of the intracellular second messenger c-di-GMP. To our knowledge, this is the first combined global analysis in a bacterium harboring three Rsm homologs. It offers a broad overview of the network of processes subjected to this type of regulation and opens the way to define what are the sequence and structure determinants that define common or differential recognition of specific RNA molecules by these proteins.